Digital Class: um modelo para a criação de cursos no paradigma de ensino híbrido - Pequeno, Henrique Sérgio Lima (2017)
The popularization of information and communication technologies (ICT) has promoted its use in educational environments such as schools and universities. However, the isolated use of technologies, without an adequate methodology, has not guaranteed an effective gain of the student in terms of learning. In the last decade, a field of research has gained prominence in the subject of the use of technologies in the educational context: Blended Learning. Blended Learning implies in the association of technologies, the experience of face-to-face and virtual teaching, promoting a new scenario that is disruptive to the classic model of education.A paradigmatic change, that has been made possible by a real experience of hybrid teaching, should modify the classroom format, transcending the scope of spatial and temporal performance.Several models of hybrid education have been established by the global academic community, yet without establishing a standard. In this sense,the current thesis presents the new conceptual model, called Digital Class, aimed at the creation of courses in the paradigm of hybrid teaching.The Model defines six dimensions that aim to truly promote a reformist behavior towards traditional teaching. Among the dimensions, we highlight the personalization of student assistance and the prediction of student performance.This model was validated in two steps: the first finished in the development of a computational architecture that implements the concepts defined by the Digital Class Model. The second one is the use of the architecture by a discipline of Physics, which belongs to the two courses of a Professional Public School of the State of Ceará.The results obtained from the validity tests of the Digital Class Model, were positive and helped to improve both the Model concepts and the Arquitecture.